Transforming diaspora in the novels of Malaysian writers of indian origin - Devarajoo, Karthiyaini (2007)
Malaysian writers of Indian origin writing in English have carved a tradition of their own in the Malaysian literary realm. The Indian diaspora in Malaysian Literature in English plays a dual-role. One is the Indian writer who is part of the diaspora himself and the other is the Indian characters that they portray in their writings. Both roles are equally significant in the contribution towards the development of literature in English in Malaysia and in its depiction of the social, political, economical, spiritual and cultural life of the Indian in Malaysia. The surge of writings in English by Malaysian Indians this millennium inevitably documents the Indian experience in Malaysia and establishes the evolving status of the Indian as a citizen of this land called home. Six novels by three Malaysian authors of Indian origin are used as a basis for texts analysis in this study of which five were published in the 21st century. The point of departure for this study is K.S.Maniam’s article “The New Diaspora”1 which calls for the ‘internationalization’ of Malaysian literature in English by writers of an up-coming community, The New Diaspora, for wider acceptance, greater recognition and broader and higher consumption globally. The diaspora is seen as a temporary transitional phase that is initially bound by ethnicity and eventually transforms and transcends ethnic, racial, regional and national boundaries to become global citizens. Taking on a socio-political approach to literary study, this study explores novels in English by Malaysian writers of Indian origin to locate the Indian diaspora, to identify the temporary transitional phase of the diaspora and to trace the transcendent transformation that supports ‘internationalization’ of communal literatures which consequently encourages and promotes global consumption.